Increased expression of the ectoenzyme CD38 in peripheral blood plasmablasts and plasma cells of patients with systemic sclerosis - Agarbati, S.; Benfaremo, D.; Viola, N.; Paolini, C.; Svegliati Baroni, S.; Funaro, A.; Moroncini, G.; Malavasi, F.; Gabrielli, A. (Frontiers in Immunology, 2022)
Objective: CD38 is a type II glycoprotein highly expressed on plasmablasts and on short- and long-lived plasma cells, but weakly expressed by lymphoid, myeloid, and non-hematopoietic cells. CD38 is a target for therapies aimed at depleting antibody-producing plasma cells. Systemic sclerosis (SSc) is an immune-mediated disease with a well-documented pathogenic role of B cells. We therefore analyzed CD38 expression in different subsets of peripheral blood mononuclear cells (PBMCs) from a cohort of SSc patients. Methods: Cell surface expression of CD38 was evaluated on PBMCs from SSc patients using eight-color flow cytometry analysis performed with a FacsCanto II (BD). Healthy individuals were used as controls (HC). Results: Forty-six SSc patients (mean age 60, range 23-79 years; 38 females and 8 males), and thirty-two age- and sex-matched HC were studied. Twenty-eight patients had the limited cutaneous form and eighteen the diffuse cutaneous form of SSc. The mean disease duration was 7 years. Fourteen patients were on immunosuppressive therapy (13 MMF, 5 RTX). The total percentages of T, B and NK cells were not different between SSc and HC. Compared to HC, SSc patients had higher levels of CD3+CD38+ T cells (p<0.05), higher percentage (p<0.001) of CD3+CD4+CD25+FOXP3+ regulatory T cells, lower percentage (p<0.05) of CD3+CD56+ NK cells. Moreover, SSc patients had higher levels of CD24highCD19+CD38high regulatory B cells than HC (p<0.01), while the amount of CD24+CD19+CD38+CD27+ memory B cells was lower (p<0.001). Finally, the percentages of circulating CD38highCD27+ plasmablasts and CD138+CD38high plasma cells were both higher in the SSc group than in HC (p<0.001). We did not observe any correlations between these immunophenotypes and disease subsets or duration, and ongoing immunosuppressive treatment. Conclusions: The increased expression of CD38 in peripheral blood plasmablasts and plasma cells of SSc patients may suggest this ectoenzyme as a candidate therapeutic target, under the hypothesis that depletion of these cells may beneficially downregulate the chronic immune response in SSc patients. Validation of this data in multicenter cohorts shall be obtained prior to clinical trials with existing anti-CD38 drugs.